Implementing the software defined management framework. (24th April 2020) - Monteiro, Maxwell Eduardo; Villaça, Rodolfo S.; Simonassi, Káio; Tavares, Renan; Reginato, Cássio
Software Defined Infrastructure (SDI) has become a relevant topic for computing and communication industry. Despite this huge technological movement, Network and Systems Management has been disregarded as one of the main themes in this ecosystem, and Software Defined Infrastructure has been managed by semi-software-defined management solutions. In order to reduce this gap, this paper presents SDMan, a Software Defined Management framework. The SDMan's proof of concept uses the OpenStack cloud platform and aims to demonstrate the feasibility of the proposed solution.